A Floristic Composition of Woody Species and Potential Carbon Storage in Reforested Sites of Sudano-Sahelian Zone of Cameroon - Konsala, Souare; Chimène, Abib Fanta; Désiré, Wadjou Bruce; Adamou, Ibrahima (International Journal of Scientific Research and Management (IJSRM), 2020)
The study examined the floristic diversity of woody species and their potential sequestration of carbon in reforested sites in sudano-sahelian zone of Cameroon. The experimental design was constituted of two blocks:  Gaban and Matchoualta sites. In each block, a transect of 40 000 m2 (1 000 m x 40 m) was established. Four circular plots of 40 m of diameter were set up along the transect, and in each plot, all the woody individuals (dbh ≥ 5 cm) were inventoried. We used Origin 6.0 to perform the statistical analyses. Phytomass, storage and carbon credit of the woody individuals were estimated on the basis of allometric equations.  At total of 3 098 woody individuals was inventoried and distributed within 62 species, 46 genera and 26 families. Fifty-six species were recorded in Gaban and fourty-nine species in Matchoualta site. Phytomass and carbon storage were 263.20 t/ha and 131.6 tC/ha for Gaban site, 213.61 t/ha and 106.80 tC/ha for Matchoualta site. The CO2 equivalent amounts were 482.97 CO2eq and 391.97 CO2eq.  The total economic values of the two reforested sites were 2 624.82 ϵ/tCO2eq; 4 112.21 ϵ/tCO2eq and 87 794 ϵ/tCO2eq respectively for Clean Development Mechanism price, Voluntary carbon price and REDD+ price. Statistical analyses revealed that carbon stock values varied significantly between the two sites (ANOVA, F = 81.80; P = 0.012).  The study provides valuable data useful for better management and monitoring of the two reforested sites with regard to tree carbon storage in mitigation of global warming and climate change.